2003
DOI: 10.1034/j.1399-3062.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the risk of hepatitis B virus reactivation after transplantation

Abstract: Numerous case reports describe patients with previously documented immunity developing active hepatitis B virus (HBV) infection after transplantation. However, the risk of reactivation of HBV under long-term immunosuppression in hepatitis B core antibody (HBcAb)-positive, hepatitis B surface antigen (HBsAg)-negative transplant recipients has not been clearly described. Herein, we present a long-term follow-up for 49 HBcAb-positive, HBsAg-negative recipients (27 liver, 18 kidney, 4 pancreas) transplanted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…The reported incidence of reactivation varies from 0% to 4%. [10][11][12]27 In this study, we observed reactivation in 6.5% of patients. The OR for reactivation in patients without anti-HBs antibodies at transplantation compared to those with anti-HBs antibodies was 26 (95% CI [2.8-240.5]).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The reported incidence of reactivation varies from 0% to 4%. [10][11][12]27 In this study, we observed reactivation in 6.5% of patients. The OR for reactivation in patients without anti-HBs antibodies at transplantation compared to those with anti-HBs antibodies was 26 (95% CI [2.8-240.5]).…”
Section: Discussionsupporting
confidence: 57%
“…These studies have also suggested that, when reactivation occurs, its consequences are benign. [10][11][12] …”
Section: Indeed Immunosuppression Affectsmentioning
confidence: 99%
“…Blanpain et al (1998) reported 2 (4%) clinically significant HBV hepatitis cases out of 49 renal allograft recipients with resolved HBV infection. Duhart et al (2003) reported no incidence of HBV reactivation in 18 anti-HBc-positive HBsAgnegative kidney recipients. They concluded that in agreement with previously published studies the risk of HBV reactivation is negligible in patients with resolved HBV infection independent of their anti-HBs status.…”
Section: Discussionmentioning
confidence: 95%
“…The risk of reactivation of HBV under long-term immunosuppression in hepatitis B core antibody-positive, hepatitis B surface antigen (HBsAg)-negative transplant recipients was evaluated over a 3-yr period in 49 transplant recipients (27 liver, 18 kidney, 4 pancreas); 37 recipients (76%) were HBsAbpositive at transplantation (165). There was no incidence of HBV reactivation defined as recurrence of HBsAg and/or HBV DNA positivity, suggesting that the risk of reactivation of HBV in hepatitis B core antibody-positive, HBsAg-negative transplant recipients was low with immunosuppression.…”
Section: Hbvmentioning
confidence: 99%